When Relationships Become Assets: A Strategic Perspective on Relationship Marketing and Customer Value Sustainability - Bintang Junita; Sonny Fransisco Siboro; Vicky Windasari; Dede Mustomi; Aprilia Puspasari (Brilliant International Journal Of Management And Tourism, 2026)
This study examines the role of relationship marketing in fostering sustainable customer value in the Indonesian fashion retail sector. The research addresses the problem of limited understanding regarding how relationship marketing practices impact long-term customer value, especially through mediating factors such as relationship quality and customer loyalty. The primary objective is to explore the direct and indirect effects of relationship marketing on customer value sustainability. A quantitative, explanatory research design was adopted, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 200 Indonesian fashion retail consumers. The results reveal that relationship marketing positively affects both relationship quality and customer value sustainability, while customer loyalty mediates the relationship between relationship marketing and customer value sustainability. Interestingly, relationship quality did not directly influence customer value sustainability, but its indirect effect through customer loyalty was significant. The study concludes that emotional connections fostered by relationship marketing, particularly through loyalty-building strategies, are key to sustaining customer value in fashion retail. These findings have practical implications for fashion retailers seeking to enhance long-term customer engagement in emerging markets.